The transience and nature of cognitive impairments in transient global amnesia: a meta-analysis - Jäger, Theodor; Bäzner, Hansjörg; Kliegel, Matthias; Szabo, Kristina; Hennerici, Michael G. (Journal of clinical and experimental neuropsychology, 2009)
Transient global amnesia (TGA) is a clinical syndrome characterized by the sudden onset of severe amnesia without concomitant focal neurological symptoms. This meta-analysis of the cognitive characteristics of TGA addressed two main issues. First, we examined the hypothesis that the acute phase of TGA is associated with changes of anterograde and retrograde episodic long-term memory sparing semantic and short-term memory, while we had no clear prediction for potential reductions of executive functions due to the relative lack of previous studies addressing this issue. Second, we analyzed the time-course of changes in cognitive functions throughout three time intervals—acute (0-24 hours after TGA onset), postacute (24 hours to 5 days), and long-term phase (5-30 days)—to reveal whether there is a fast versus a delayed recovery. The results of the meta-analysis on 152 effect sizes from 25 studies showed that TGA is characterized by an extraordinarily large reduction of anterograde (d• = 1.89) and a somewhat milder reduction of retrograde (d• = 1.28) episodic long-term memory. Moreover, our results indicate the existence of additional, nonamnestic cognitive changes during TGA, because executive functions were also diminished (d• = 0.79). Reductions in both anterograde episodic long-term memory and executive function recover slowly, as slightly poorer performance in these cognitive domains can be found in the postacute phase (d•s = 0.32 and 0.44). All cognitive diminutions resolved within the long-term phase, by this calling into question previous reports of poorer performance of TGA patients relative to comparison subjects weeks or months after the attack.
Published online: 16 Dec 2008
Gesehen am 17.03.2021